Comparison and analysis of energy loss and flow characteristics of T-junctions via secondary flow and entropy production. (November 2022) - Yin, Yifei; Li, Angui; Wu, Dingmeng; Wen, Xiaoqi; Li, Jiaxing; Guo, Jinnan; Ma, Yuanqing
Abstract: The energy loss and resistance effect of traditional local components widely used in HVAC systems in buildings are severe. To improve the significant energy loss effect, a method to reduce resistance and energy loss by inserting guide vanes in a confluent T-junction is proposed through full-scale experiments and numerical simulations, and the flow characteristics and energy loss distribution of the T-junction are analysed through the swirl intensity of the secondary flow and the entropy production principle. The energy loss reduction rates (ELRRs) of T-junctions are compared under different diameter ratios, branch angles, and flow ratios. The results show that the total energy loss coefficient of the T-junction with curved guide vanes is significantly smaller than that of the traditional T-junction. The maximum ELRR is 43.5% when the diameter ratio is 0.8 and the flow ratio is 0.2. The insertion of a guide vane cuts the large vortex into multiple small vortices, thereby weakening the entropy production and swirl intensity of the downstream secondary flow. Under different Reynolds numbers, the effect of the guide vane on reducing the resistance and energy loss of the T-junction is verified by full-scale experiments, and the experimental results are in excellent agreement with the simulation results. This study provides data support and a reference for the standardized and design of low-energy loss T-junctions in HVAC systems for the energy-saving operation of buildings. Highlights: A low-energy loss T-junction with a guide vane is investigated by experiments and numerical simulations. The guide vane can cut the large vortex into multiple vortices with smaller swirl intensities. Inserting guide vanes at suitable locations in the T-junction reduces entropy production. T-junctions with guide vanes can reduce the energy loss coefficient by up to 43.5%.